Nivolumab Combined With Ipilimumab Treatment Induced Hypophysitis and Immune-Mediated Liver Injury in Advanced Esophageal Squamous Cell Carcinoma: A Case Report - Feng, Yi; Li, Chengyang; Ji, Yuan; Liu, Ying; Gan, Lu; Yu, Yiyi; Liu, Tianshu (Frontiers in Oncology, 2022)
Immune check point inhibitors (ICPis) become more frequency therapy strategy because of the impact in killing tumor cells by reactivating the activity of immune cells. Because CTLA-4 antibody and PD-1 antibody (or PD-L1 antibody) work in different way, they have synergistic effects when used in combination in many cancers. However, it has been found that a strong immune response may lead to more serious and multi-system immune-related adverse events (irAE). We describe an advanced esophageal squamous cell carcinoma patient received nivolumab combined with ipilimumab resulting in hypophysitis and immune-mediated liver injury. He was enrolled into a CheckMate 648 global, multicenter, randomized phase 3 Clinical Trial (CTR20171227) investigating the combined potency of nivolumab and ipilimumab in the treatment of patients with advanced esophageal squamous cell carcinoma and admitted to our center (site 0200). The patient developed hypophysitis and immune-related hepatitis rapidly after anti-immune therapy, leading to the interruption of anti-tumor therapy. And then the patient developed Herpes zoster and recurrence of tuberculosis after treatment of irAEs with glucocorticoids. We report this case in the hope that doctors need to have sufficient knowledge and attention to the occurrence of irAE during the anti-immune combination therapy and actively intervene as soon as possible to obtain better anti-tumor effects and less harm to patients.